A discourse analysis of news items on the east sea issues from 2012 to 2014 in english and vietnamese newspapers - Huỳnh,Tấn Sỹ (ĐHĐN., 2015)
This study made an investigation into news items on the East Sea issues in English and Vietnamese newspapers (ENIESIs and VNIESIs) in order to discover discourse features and find out the similarities and differences between them in terms of the layout, lexical features, syntactic structures and cohesive devices. The findings of this study are presented based on a survey of 50 news items in English newspapers and 50 ones in Vietnamese newspapers which are taken from the well-known websites such as the BBC, the Washington post, the Thanhnien, the Tuoitre, the Quandoinhandan... Thanks to the combinations of qualitative and quantitative approaches, the discourse features of NIESIs in both languages were analyzed and compared. In terms of layout, both ENIESIs and VNIESIs fix the suggested template by Nguyễn Hòa, which is composed of four components: background, elaboration/evidence, result, and comment. The lexical choice in the thesis focused on words denoting tension and collision between Vietnamese and Chinese guard forces. Words denoting tension in both ENIESIs and VNIESIs could be either nouns with tense property itself or nouns combined from a neutral noun and an adjective expressing tension. 100% of words denoting collision in ENIESIs were transitive meanwhile 98.45% of those were transitive in VNIESIs. In terms of syntactic features, direct and indirect speeches; sentence types were investigated. English writers tended to balance the use of direct and indirect speeches in their news items (44.5% and 55.5%), comparing with a different propotion in VNIESIs (28.4% and 71.6%). Both writers of ENIESIs and VNIESIs used simple sentences with highest percentages, followed by complex sentences and then compound sentences. In terms of cohesive devices, the grammatical and lexical cohesion occupied 88.4% and 11.6% in ENIESIs respectively. A much different proportion, 44.4% and 55.6% was found in VNIESIs.